The safety of hepatectomy after transarterial radioembolization: Single institution experience and review of the literature. Issue 6 (13th July 2020) - Noda, Christopher; Williams, Gregory A.; Foltz, Gretchen; Kim, Hyun; Sanford, Dominic E.; Hammill, Chet W.; Fields, Ryan C.
Abstract: Background and Objectives: The liver is a frequent site of malignancy, both primary and metastatic. The treatment goal of patients with liver cancer may include transarterial radioembolization (TARE). There are limited reports on the safety of hepatectomy following TARE. Our study's purpose is to review patients who have received TARE followed by hepatectomy. Methods: A retrospective study was performed on patients diagnosed with any liver cancer from 2013 to 2019 who underwent TARE followed by hepatectomy. Postoperative complications were prospectively collected. Descriptive statistics and the Kaplan‐Meier test were used to assess survival outcomes. Results: Twelve patients were treated with a TARE followed by a hepatectomy (nine with ≥4 segments resected). Diagnoses included: six HCC, four cholangiocarcinoma, one metastatic neuroendocrine tumor, and one metastatic colorectal cancer. There were no 90‐day post‐hepatectomy mortalities and the overall morbidity was 66% (16% severe ≥MAGS 3). Hepatectomy‐specific complications after hepatectomy included two (16%) bile leaks and no post‐hepatectomy liver failures. The median recurrence free survival was 26 months. Overall survival at 1‐year was 78% and at 3 years was 47%. Conclusions: Our results support the safety of hepatectomy in select patients after TARE. Additional comparison to patients who receive hepatectomy as a first‐line treatment for liver cancers should be investigated.